Innovative Modeling Techniques for Predictive Medicine - Pires, Marília (2016)
Mathematical modeling and simulations in the Life Sciences is a very ambitious and rapidly developing interdisciplinary research field that connects mathematics, computational sciences and engineering to biology and medicine. Starting from high-resolution volumetric medical imaging, the development of spatially realistic physiological models for predictive medicine leads to complex mathematical models to capture heterogeneous processes of multiscale nature, that require highly efficient numerical algorithms and high performance computing techniques for their simulation.